As Tecnologias digitais e a prática docente no ensino médio de biologia : um estudo de caso. - Gomes, Lincoln César Fernandes (2018)
In today's world, digital information and communication technologies (TDICs) are present in almost all social relationships and have been significantly changing the way people live together in homes or work relationships, and Education is not foreign to that. In Education, the TDICs are increasingly entering teaching practices with the promise of facilitating themediation of the various programmatic contents. The High School of Biology, which in itself brings a complexity of concepts and phenomena, can be benefited by the use of digital technologies by teachers. Therefore, it is necessary to elucidate the real contribution that the TDICs can give to the process of teaching and learning Biology in High School. In this inteire we have the general objective of this research that was to analyze the perceptions of teachers of Biology of High School related to the use of digital technologies in their teaching practice identifying which digital technologies they appropriate in their teaching praxis. The data collection was performed through a semi-structured interview and the discussion of the results obtained was mainly through the content analysis of Bardin (1977). This research was carried out in a private school in the city of Fortaleza-CE and the subjects of the research were the teachers of Biology of the Secondary School. As an educational product, a Virtual Learning Environment (VLE) was developed to enable the ongoing training of Biology teachers in the pedagogical use of digital technologies. This AVA allows the exchange of experiences among the biology teachers themselves in this cyberspace regarding the pedagogical use of digital technologies in their teaching practice and, thus, makes it possible to construct in a collaborative way among their peers a new look at the insertion of the TDICs in the process of teaching and learning in Biology in High School, because it was possible to verify that the teachers studied are still reluctant to use the digital technologies frequently because they do not have adequate training for this and their use still occurs in disarray with the pedagogical aspects.